Lessons learnt from historical land use changes? Application of the WATEM/SEDEM erosion model to the Kali Basin, Balaton Highlands, Hungary - Jordán, Győző; Szilassi, Péter; van Rompaey, Anton (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
Historical land use changes may have significant impact on erosion and agricultural soil properties, including soil degradation by acidification, nutrient leaching and organic matter depletion. The Kali Basin, situated in the area of the Balaton Uplands National Park, with its historical agricultural records, together with the available unique historical land use data for the last 200 years, provides an excellent opportunity to study and model impacts of historical land use changes on erosion and agricultural soil properties. Application of the SEDEM/WATEM distributed erosion and sediment transport model showed that, despite the low overall sediment export from the catchment, the land use changes introduced by property ownership and agricultural changes have decreased the average soil erosion in the catchment but have increased the amount of sediment exported to the Lake Balaton. This is due to changes in the land cover pattern that allow more sediment to be transported to the river system. The overall conclusion of this study is that besides the size and area proportion of land use types, land use pattern seems to be equally important in soil erosion and degradation processes, thus land use pattern is a key factor for landscape planning and development in the Kali Basin.